Catch composition and catch per unit effort of different fishing gears operating around the three marine protected areas in the Island Garden City of Samal. - Ballesteros, Arturo III S. (2010)
Marine protected areas (MPAs) have been created to provide sustainable fisheries. It is important to monitor the effect of these MPAs among fisherman especially in Davao Gulf area. Three MPAs namely sanipaan MPA, Coral Garden MPA and Aundanao MPA were investigated from December 2008 to December 2009 to determine its contribution to the local reef fishery. Aside from the actual studies on the present standing stocks of commercially important species, a Focus Group Discussion (FGD) and a field survey was conducted last July 2009. Through the FGD and field survey, the commonly operating gears around the three MPAs were identified as Gill net, kawil (simple), kawil (multiple), spear, pamo (driftgill net), sarangat (squid jig), bintol (crablift net) and undak (multiple hook and line). the commonly caught fish belongs to the family Acanthuridae (surgeonfishes), Caesionidae (fusliers) Carangidae (jacks), Clupeidae (sardines), Engraulidae (anchovies), Haemulidae (sweetlips), Holocentridae (squirrelfishes and soldierfishes) Labridae (wrasses), Letrinidae (emperors), Menidae (moonfish), Mugilidae (mullets), Mullidae (goatfishes), Scaridae (parrotfishes), Scombridae (makerels and tunas), Scorpaenidae (scorpionfishes or rockfishes) Serranidae (groupers) and Siganidae (rabbitfishes). The catch in sanipaan is composed of 60% reef fishes and 40% pelagic fishes. In coral garden, it is composed of 10 to 20%reef fishes and 80 to 90 % pelagic species while in Aundanao, 60 to 80% of the catch was composed of reef fishes ehile the rest is composed of reef fishes while the rest is composed of reef fishes. Declining catch was observed in the trend line established but a gradual increase in the annual catch was observed upon the establishment of MPAs . At present pamo has the highest CPUE (10kg.trip-!). The lowest CPUE was observed in undak (0.83kg.trip-1). The gear with the highest total annual catch was gill net (672.85 mt.yr-1) followed by kawil (multiple) 402.63 mt.yr -1) and kawil (simple) (241s.82 mt.yr-1). The lowest annual catch was observed in the gear undak (0.8 mt.yr-!) . With the data gathered, it was concluded that the MPAs have significant contribution to the increase of catch rates of fishers in the area through spill-over effect.